Heterostructure-induced light absorption and charge-transfer optimization of a TiO₂ photoanode for photoelectrochemical water splitting - Yi, Qinghua (2022)
Rutile titanium dioxide (TiO2) exhibits excellent photoelectrochemical properties but limited photocatalytic performance due to its large band gap and fast electron-hole recombination. Here, we report a composite catalyst of NiTiO3 nanoparticle-coated TiO2 nanorod arrays (NiTiO3/TiO2 NRAs) via an electrostatic assembly strategy. The NiTiO3/TiO2 heterostructure endows an enlarged absorption range and enhanced electron-hole separation efficiency. When being used as an electrode in photoelectrochemical water splitting, it achieves the highest photocurrent density of 1.94 mA cm-2 at 1.0 V versus reversible hydrogen electrode, which is 3.74 times higher than the photocurrent density of pristine rutile TiO2 NRAs (0.51 mA cm-2). The heterostructure engineering strategy is demonstrated to enhance the photoelectrochemical performance, which can be extended to optimize various semiconductor photocatalysts.